Metode SWARA dan Multi Attribute Utility Theory Untuk Penentuan Pemasok Pakan Ikan Terbaik - Agung Deni Wahyudi; A. Ferico Octaviansyah Pasaribu (CV. Keranjang Teknologi Media, 2023)
Problems in the selection of fish feed suppliers there is no model of a decision support system in assessing supplier performance based on purchase transactions made. This study aims to apply the SWARA method in weighting the criteria used in selecting the best fish feed suppliers and then using the MAUT method to determine the best fish feed suppliers. Multi Attribute Utility Theory (MAUT) is a sophisticated and systematic decision-making framework, designed to deal with complexity and uncertainty in the context of multi-criteria evaluation. Weighting in the Step-wise Weight Assessment Ratio Analysis (SWARA) method plays a key role in assigning relative values to the criteria used for multi-criteria decision making. The results of the fish feed supplier selection ranking show that the first rank with a total final utility value of 0.5795 was obtained by Supplier 3, the second rank with a total final utility value of 0.5275 was obtained by Supplier 8, and the third rank with a total final utility value of 0.3865 was obtained by Supplier 6.